2010
DOI: 10.1111/j.1440-1746.2010.06377.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α‐secreting CD16+ antigen presenting cells are effectively removed by granulocytapheresis in ulcerative colitis patients

Abstract: The effect of GCAP in peripheral blood APC consisted mainly on a significant depletion of tumor necrosis factor-α secreting CD16-mDC. This finding could suggest a potential mechanism of GCAP beneficial effect that must be confirmed in larger series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…GMA is an extracorporeal therapy using a column filled with cellulose acetate beads, which adsorbs 28.3% of granulocytes, 18.1% of monocytes, and 7.8% of lymphocytes from blood in the column (6). It has been reported that CD16+ myeloid dendritic cells (mDC), activated in ulcerative colitis, are removed by GMA, probably resulting in a reduction in serum TNF-α levels (7). Adsorptive depletion of CD14+/CD16+ mDC may suggest a mechanism for the beneficial effect of GMA in pustular psoriasis (8).…”
Section: Discussionmentioning
confidence: 99%
“…GMA is an extracorporeal therapy using a column filled with cellulose acetate beads, which adsorbs 28.3% of granulocytes, 18.1% of monocytes, and 7.8% of lymphocytes from blood in the column (6). It has been reported that CD16+ myeloid dendritic cells (mDC), activated in ulcerative colitis, are removed by GMA, probably resulting in a reduction in serum TNF-α levels (7). Adsorptive depletion of CD14+/CD16+ mDC may suggest a mechanism for the beneficial effect of GMA in pustular psoriasis (8).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pDC could induce the differentiation and activation of Treg, thus directly or indirectly inhibit a variety of helper T cells 20 . CD16‐mDC in mDC can secrete TNF‐α factor, and the combination of TNF‐α and TLR2 ligand can differentiate CD16‐mDC into mature DCs with high antigen‐presenting ability 21 . The flow cytometry of NK cell and DCs subsets in our ITP patients was further analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…GMA has emerged as a potential therapeutic option for refractory IH cases . Its effects are attributed to the elimination of activated neutrophils and monocytes in the peripheral blood …”
Section: Discussionmentioning
confidence: 99%